Pengembangan Sistem Informasi Quality Control Menggunakan Metode Waterfall Pada PT. Rudolf Chemicals Indonesia - Arif Siswandi; Encep Hambali (Jurnal SIGMA, 2022)
Abstract The quality control department in practice is often related to the logistics department where there are often delays in receiving information on the arrival of raw material products, product quality information and write transactions. In addition, there is often a delay in information about product standard specifications received by the quality control department from R&D which has an impact on delays in checking by the quality control party. Because of this problem, the author developed a quality control information system to facilitate the transfer of information both between the quality control and logistics departments or between the quality control and R&D departments. In the development of the information system itself, there are several software development methods, namely structured design, rapid application development and agile development. One of the structured design methods that is still in use today is the waterfall method. Where this method identifies system requirements long before programming begins, thereby minimizing changes to requirements while the project is running. The results show that after the development of the quality control information system, the business processes in the quality control department became faster and more efficient. Keywords: Quality Control; Information Systems; Waterfall